PENILAIAN DOMAIN SOSIAL EKONOMI DARI PENDEKATAN EAFM PADA PERIKANAN LEMURU DI PERAIRAN SELAT BALI - Tanjov, Yulia Estmirar; Larasati, Rakhma Fitria; Suhery, Noveldesra; Astika, I Made Ageng (Jurnal Teknologi Perikanan dan Kelautan, 2024)
Bali Sardinella (Sardinella lemuru) is a small pelagic species that is the focus of commercial fisheries and the primary target catch for fishermen at the fishery port of Pengambengan. This research aims to assess the management status of the Bali Sardinella fisheries at the fishery port of Pengambengan based on social and economic domains using the Ecosystem Approach to Fisheries Management (EAFM). This study is a survey research with a quantitative descriptive approach, using interviews and observations as data collection instruments. The data are obtained from interviews and observations of fishermen at the fishery port of Pengambengan. Fishermen respondents were randomly selected and considered representative, focusing on the lemuru species caught using purse seine fishing gear. Data analysis uses the EAFM analysis on social and economic domains, the flag model technique, and management actions for Bali Sardinella in the Bali Strait Waters. In terms of the social domain, fishermen at the fishery port of Pengambengan had a high category and were given a green flag, while in the economic domain, fishermen in the fishery port of Pengambengan fell into the low category, thus being given a red flag. The management actions for Bali Sardinella fisheries in the Bali Strait Waters, particularly those landed at PPN Pengambengan, are prioritized in the economic domain by increasing household income and savings ratio to improve the future economic condition of the fishermen at PPN Pengambengan.